COD (glucose configuration) effects on the non-Darcy flow of compacted clay in a municipal solid waste landfill. (1st February 2019) - Wang, Shengwei; Zhu, Wei; Fei, Kang; He, Haipeng; Fu, Gaofeng; Shu, Shi; Song, Jian
Graphical abstract: Highlights: As leachate COD concentration increases, k is increasing and i0 is decreasing. As the COD concentration increased, the bound water decreased. As the COD concentration increased, μ increased and K decreased. The new equations to calculate k and i0 with COD concentration were proposed. Abstract: Clay liners play a critical role in preventing leachate leakage and pollutant migration from landfills through their low permeability and non-Darcy behavior during seepage, and such liners exhibit a threshold-gradient characteristic. Landfill waste may produce complex, highly concentrated leachates through chemical and biological degradation. The hydraulic conductivity and threshold gradient of a clay liner is affected by high leachate concentrations. Some scholars have suggested that chemical oxygen demand (COD) can be selected as a key indicator for pollution alerts and used to assess the environmental risk posed by municipal solid waste (MSW) landfill sites. To study the influence of leachate concentration on the permeability of compacted clay, the highest concentrations of organic pollutant COD (glucose configuration) were used as the target dialysate in this study. COD is abbreviation of chemical oxygen demand. A COD solution was prepared from dissolved glucose for the experiments. The results showed that as the COD concentration increased, the hydraulic conductivity increased and the threshold gradient decreased. The permeate viscosity and the soil-water characteristic curve were measured. As the COD concentration increased, the permeate viscosity increased and the bound water content decreased. By considering the COD concentration effects on permeate viscosity and intrinsic permeability and adapting a previously established empirical relationship between the threshold gradient and apparent fluidity ( K / η ), this study derived an equation for calculating the hydraulic conductivity and threshold gradient with changes in the COD concentration, and good predictions were obtained.